EVALUASI USABILITY PADA APLIKASI WETV MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) DAN THINK ALOUD - Sang Putu Aris Wesnawa; Made Arista Amelia; Michael Juary Humala (Jurnal Riset Multidisiplin Edukasi, 2025)
The use of information technology in the field of Streaming Media has developed rapidly, allowing users to access various shows via mobile applications and web browsers. This service gives you the freedom to watch movies, television series and other video content anytime and anywhere. One of the popular applications in this field is WeTV. WeTV offers a variety of content, including dramas, films and variety shows from various countries, both local and international, so users can enjoy shows from all over the world. In the 13 years since the WeTV application service has been running, there are still users who complain about using WeTV, one of which is that there are too many advertisements that appear when watching films. So it is necessary to carry out user-based evaluation. The User Experience Questionnaire (UEQ) covers six aspects with 26 statement items. UEQ data analysis was carried out using the UEQ Data Analysis Tool by comparing the value of each aspect with the available product data set. In UEQ, 5 respondents will be involved to get user satisfaction scores. Think Aloud evaluation involved 5 respondents based on UEQ results. In this study, 5 task scenarios were used which were adapted to the existing functionality. The results of the analysis show that the aspects of attractiveness, clarity, efficiency, accuracy, stimulation are in the poor category and novelty is in the below average category. The results of the analysis show that priority improvements can be focused on all aspects. The average value for each aspect is as follows: attractiveness aspect is 0.27; clarity aspect of 0.55; efficiency aspect of 0.30; accuracy aspect of 0.75; the stimulation aspect is 0.45 and the novelty aspect is 0.70. The Think Aloud evaluation results succeeded in obtaining 4 problems raised by respondents.